POLYPHENOLS FROM DARK CHOCOLATE AND THEIR - naimbar, vanisha (International Journal of Pharmaceutical & Biological Archive, 2010)
Dark Chocolates (DC) in recent years have gained greater significance & are recommended in the list of functional foods due to the polyphenols (Catechin, Epicatechin and Procyanidins) present in them. The present study is aimed at investigating the polyphenol profile, fat as well as fatty acid profile of dark chocolate available in India and the impact of 50 g DC consumption for a period of 1 month on the nutritional as well as lipid profile of Gujarati Jain subjects. Forty [20 Exp. (M=10, F=10) & 20 Controls (M=10, F=10)] free living healthy Gujarati Jains (30-55yrs of age) were selected for the present study. Pre and post data were elicited on the socio-economic status, anthropometry, dietary pattern, FBS and lipid profile. DC supplementations lead to a reduction of TC (12%), LDL (17.7%) and Non HDL- C (20.0%) (p< 0.05) of the Experimental Group as compared to the Control group. However an overall significant increase in the WC (1.9 cm, (p < 0.05) & marginal increase in WHR (0.91 vs.0.94) was recorded. These findings indicate that though the polyphenols in dark chocolates had a positive impact on the lipid parameters, DC should be used only as substitutes and not as an addition to the sweets in the daily diets.